Exploring the Correlation Between Metacognitive Skills and Cognitive Learning Outcomes Across Various Biology Learning Models in High Schools - Ninik Kristiani; Herawati Susilo; Duran Corebima Aloysius; Fatchur Rohman (Jurnal Pendidikan Sains, 2023)
In Malang City, a notable observation within the realm of high school biology education suggests a prevalent lack of metacognitive knowledge among teachers, hindering their efficacy in nurturing students' metacognitive capacities. Such deficiency yields implications for diminished cognitive abilities among students. Recognizing this, there emerges a pressing need for an enhanced pedagogical framework capable of fostering metacognitive skills adeptly. One promising approach involves integrating inquiry-based learning and problem-based mindful pedagogy (PBMP). This amalgamation is anticipated to synergistically harness the potential of both methodologies in bolstering metacognitive skills alongside cognitive learning outcomes. This study adopts a correlational research design, wherein data encompassing metacognitive skills and cognitive learning outcomes are systematically gathered. Methodologically, the evaluation entails the integration of metacognitive skills assessments with cognitive learning outcome metrics. Subsequent analysis is conducted via regression analysis, employing a significance threshold of 5%. Statistical examination is facilitated through the utilization of SPSS 17.0 for Windows. The findings of the analysis unveil a discernible relationship between metacognitive skills and cognitive learning outcomes across distinct biology lessons. Notably, the extent of metacognitive skill contribution to cognitive learning outcomes exhibits variance. Particularly noteworthy is the pronounced impact observed within the Inquiry-PBMP class setting, indicating its superiority over alternative pedagogical models in cultivating metacognitive skills and subsequently augmenting students' cognitive learning achievements.DOI: 10.17977/jps.v11i32023p092